2022
DOI: 10.3390/su141912163
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Drivers towards Electric Vehicles in Kuwait

Abstract: Although researchers have started to examine the landscape of electric vehicles (EVs) around the world, very little research has examined this phenomenon in Kuwait. In addition, limited research has explored it among drivers. Kuwait constitutes a very promising market for EVs because there is a need to lower GHG emissions and improve the air quality in Kuwait. This study therefore explored the attitudes of conventional car internal combustion engine (ICE) drivers towards EVs in Kuwait, particularly identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…This group favors the soundless engine and lack of maintenance due to its environmental friendliness. The majority of Tesla model Y and model 3 drivers are male, as women in Kuwait are reluctant to purchase vehicles without a dealership [8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…This group favors the soundless engine and lack of maintenance due to its environmental friendliness. The majority of Tesla model Y and model 3 drivers are male, as women in Kuwait are reluctant to purchase vehicles without a dealership [8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond functional attributes and service infrastructure, demographic factors such as age, gender, education, family size, and household income, and psychological factors also significantly affect consumer preference and WTP for NEVs [8,[43][44][45][46][47]. Jansson et al [48] identified several key psychological drivers behind the adoption of NEVs, including interpersonal influence and attitudinal factors.…”
Section: Willingness To Pay For Nev Attributesmentioning
confidence: 99%
“…However, this subject remains pertinent for emergent market nations due to the relatively recent transition to renewable energy and fuel alternatives. [61] Emerging market countries will continue to find environmental impact analysis to be a pertinent subject, and we sincerely hope that editors will maintain their interest in this area.…”
Section: Environmental Analysis Of Driving Electric Vehiclementioning
confidence: 99%